Decision-delivery intervals: Impact of a colour code protocol for emergency caesareans. (March 2020) - Le Mitouard, Marine; Gaucher, Laurent; Huissoud, Cyril; Gaucherand, Pascal; Rudigoz, René-Charles; Dupont, Corinne; Cortet, Marion
Abstract: Objective: Assess the impact of implementation by simple distribution of a "colour code" protocol for emergency caesareans on the course over time of the "decision-delivery interval" (DDI) and neonatal outcome. Design: Observational study in 26 maternity units of the AURORE perinatal network, conducted between October 1, 2017, and April 30, 2018. Each maternity ward́ was supposed to prospectively include 20 consecutive cases of caesareans performed either as an emergency, that is, as a code orange, or an extreme emergency, that is, code red. We compared the DDIs observed in 2017 to those in 2007 according to the degree of emergency, the maternity unit level of care, and their adherence to the protocol. Neonatal outcome in 2007 and 2017, assessed from laboratory and clinical indicators, was also compared, overall and according to the degree of emergency. Results: The DDI was significantly lower in 2017 (n = 478) than in 2007 (n = 447), regardless of the degree of emergency and the level of care (p < 0.0001). In 2017, all code red caesareans were performed in less than 15 min in level 3 maternity units compared with 73 % (p = 0.039) in 2007. Fewer than 20 % of the caesareans in the 2007 study period were performed in less than 15 min in level 1 and 2 maternity units. Today, this is the case for 83 % of these caesareans in level 2 units (p < 0.001) and 36 % in level 1 (p = 0.01). In 2017, code orange caesareans were performed in less than 30 min in 96 % of cases in level 3 units, 67 % in level 2, and 33 % in level 1, compared respectively with 67 % (p = 0.015), 25 % (p < 0.0001) and 16 % (p = 0.0003) in 2007. We did not observe any difference in the neonatal outcome between 2007 and 2017 or as a function of the DDI expected based on the caesarean colour code. Conclusion: The implementation of the colour code protocols was associated with an improved DDI and better adherence to the recommendations in all 26 maternity units in this perinatal network.